2018
DOI: 10.1039/c8ra03075h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photoluminescence properties of Eu3+-activated LiCa3ZnV3O12white-emitting phosphors

Abstract: Single-component white-emitting phosphors are highly promising for applications in phosphor-converted white light-emitting diodes. In this paper, novel single-phase LiCa 3(1Àx)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 69 publications
0
18
1
Order By: Relevance
“…Luminescence studies revealed strong, broad excitation bands ranging between 250 and 400 nm, with a peak centred at λ = 343 nm due to the VO 4 3− ion. The ET mechanism occurred due to transfer of energy from the LCZV host to Eu 3+ ions, as shown in Figure . The contribution of a broad bluish‐green emission band and red emission lines from Eu 3+ in the LCZV:Eu 3+ phosphors provided a bright tunable white light under 343 nm excitation.…”
Section: Development Of New Phosphorscontrasting
confidence: 67%
“…Luminescence studies revealed strong, broad excitation bands ranging between 250 and 400 nm, with a peak centred at λ = 343 nm due to the VO 4 3− ion. The ET mechanism occurred due to transfer of energy from the LCZV host to Eu 3+ ions, as shown in Figure . The contribution of a broad bluish‐green emission band and red emission lines from Eu 3+ in the LCZV:Eu 3+ phosphors provided a bright tunable white light under 343 nm excitation.…”
Section: Development Of New Phosphorscontrasting
confidence: 67%
“…Therefore, the concentration quenching mechanism was the non-radiative energy transfer among the adjacent Mn 4+ ions in SGA:Mn 4+ phosphors, which was similar to the previous research. 53,[61][62][63] Fig . 5 illustrates the CIE chromaticity diagram of SGA:0.1%Mn 4+ sample.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to conventional lighting sources such as incandescent and uorescent lamps, WLEDs have attracted great attention owing to their numerous advantages such as small volume, low power consumption, high brightness, better exible design, reliability, long persistence and eco-friendly nature. [1][2][3][4][5][6][7][8][9] There exists a deciency of red components in the commercially available WLEDs composed of blue emitting InGaN LED chips coated with a yellow Y 3 Al 5 O 12 :Ce 3+ phosphor. 10,11 Nevertheless, some factors that are involved in reducing the quality of white light include a low color rendering index (CRI), high correlated color temperature (CCT), thermal quenching, blue-halo effect and current dependence of chromaticity.…”
Section: Introductionmentioning
confidence: 99%